Implementasi Lembaga Pengendali Mutu Pendidik di Lembaga Pendidikan Islam: Implementation of Educator Quality Control Institutions in Islamic Education Institutions - Bashori, Abdul Hamid; Alisha, Moh. Nafi’; Jalaluddin, Moh. (Thawalib: Jurnal Kependidikan Islam, 2024)
The educator quality assurance institution was established to ensure the quality of educators in educational institutions. The research aims to analyze and explain the planning, implementation, evaluation, and follow-up of the Educator Quality Control Institution at Maktuba Al-Majidiyah Islamic Education Institution in Pamekasan. This research uses a qualitative research approach with a case study research design. Meanwhile, the informants are: the general chairman of the education council, the education council, and personnel management. Data were collected using observation, interviews, and documentation techniques. Data analysis consists of three stages: data reduction, data display, and conclusion drawing. Research findings: (1) educator planning: setting standards, recruitment, selection, and placement of educators. (2) educator implementation: supervisor, motivator, trainer, developer, and compensator. (3) educator evaluation: monitoring educator activities by comparing standards with performance. (4) follow-up: rewards and punishments. Conclusion: the educator quality assurance institution has performed its tasks well because it has managed educators effectively. Research contribution: it can enhance the quality of educator management.